An Examination of Middle School Students' Mathematical Identities in a Social Context - İsmail Satmaz; Remzi Y. Kıncal (Educational Academic Research)
This study examines the mathematical identities of middle school students in a social context. Mathematical identity is an important factor affecting students' relationships with mathematics and their success in mathematics. Identity is formed by individuals' interactions with their perceptions and environment. In this context, mathematical identity is also shaped by social environment, education system, socio-cultural norms, and socio-economic status. In this research, the case study design, one of the qualitative research methods, was used. This research was conducted with 24 middle school students studying in different six public schools in a provincial center in the Marmara Region in the 2023-2024 academic year in Turkey, and 24 relatives determined by these students. The participants were selected through the maximum diversity sampling method. In the data collection stage, the "Mathematics Identity Scale" and the "Mathematics Identity Social Context Interview Form" developed by the researchers were used. The data were analyzed through a content analysis method. Findings indicate that themes such as attitudes toward the social environment, education system, socio-cultural norms, and socio-economic status significantly affect students' mathematical identities. In addition, it has been determined that individual characteristics such as mathematical communication skills, mathematical literacy, attitude towards mathematics, and mathematical persistence also affect the formation of mathematical identity. In conclusion, students' social environments and individual characteristics play a significant role in shaping their mathematical identities. Researchers are recommended to conduct similar studies in different social and cultural contexts and to examine the changes in students' mathematical identities through longitudinal studies.